Three-point vs one-point palpation of temporomandibular joint. A clinical trial study - A Kheder Khrwatany, Khurshid; H Shekhani, Farman; Qader Ahmed , Jamal (Diyala Journal of Medicine, 2022)
Background: Palpation is a crucial component of the temporomandibular joint (TMJ) examination in identifying tenderness. One-finger one-point palpation has a high tendency for inappropriate application and misinterpretation. Objective: To evaluate three-point vs one-point palpation in determination of TMJ tenderness. Patients and Methods: The study included fourth and fifth-year students in the College of Dentistry/Hawler Medical University. All students were examined using both one-point and three-point techniques. Two essential elements were recorded for each TMJ: tenderness and clicking. Results: A total of 76 students (152 TMJs); 40 female and 37 male, were included. One-point TMJ tenderness was present in 41 (26.7%) and three-point TMJ tenderness was present in 114 (75%) TMJs (P=0.0001), with a sensitivity of 75% and specificity of 73%. Clicking, in three-point, 14 (9.21%), in one-point, 22 (14.47%) TMJs were with (P=0.2136) with a sensitivity of 18.42% and specificity of 71%. Conclusion: Three-point technique can be used for palpation of TMJ, especially for detection of joint tenderness. Better not to be used for clicking evaluation.